On understanding the chip formation mechanism of TiBw/TA15 composites with network architecture in micro cutting. (15th December 2021) - Yang, Minghui; Zhou, Lin; Peng, Fangyu; Deng, Ben; Huang, Yu; Rong, Yan
Abstract: The TiBw/TA15 composites with network architecture have potential applications in the aerospace and automobile industry. In this paper, the in-situ high-speed imaging of the cutting zone at the micro-scale and digital image correlation analysis of the image sequences were conducted. And the qualitative analysis of chip characteristics was performed. The influences of material microstructures and undeformed chip thickness on workpiece deformation behaviors were discussed. The experimental and analytical results indicated that when the undeformed chip thicknesses (10 μm and 20 μm) were much smaller than the network size (about 100 μm), the influences of matrix microstructures on the chip formation were predominant through the ductile fracture mode. With the increase of undeformed chip thicknesses (40 μm and 60 μm), the influences of network-structured TiBw reinforcements on the fracture modes and shear band formation were intensified, the brittle fractures occurred along the TiBw-rich region in the transcrystalline mode when cutting across the network boundary.